Multicenter retrospective analysis of systemic chemotherapy for advanced neuroendocrine carcinoma of the digestive system. Issue 9 (6th September 2014) - Yamaguchi, Tomohiro; Machida, Nozomu; Morizane, Chigusa; Kasuga, Akiyoshi; Takahashi, Hideaki; Sudo, Kentaro; Nishina, Tomohiro; Tobimatsu, Kazutoshi; Ishido, Kenji; Furuse, Junji; Boku, Narikazu; Okusaka, Takuji
<x xml:space="preserve">Abstract</x> This study analyzed outcomes of systemic chemotherapy for advanced neuroendocrine carcinoma (NEC) of the digestive system. Clinical data from 258 patients with unresectable or recurrent NEC of the gastrointestinal tract (GI) or hepato‐biliary‐pancreatic system (HBP), who received chemotherapy, were collected from 23 Japanese institutions and analyzed retrospectively. Patients had primary sites in the esophagus (n = 85), stomach (n = 70), small bowel (n = 6), colorectum (n = 31), hepato‐biliary system (n = 31) and pancreas (n = 31). Median overall survival (OS) was 13.4 months the esophagus, 13.3 months for the stomach, 29.7 months for the small bowel, 7.6 months for the colorectum, 7.9 months for the hepato‐biliary system and 8.5 months for the pancreas. Irinotecan plus cisplatin (IP) and etoposide plus cisplatin (EP) were most commonly selected for GI‐NEC and HBP‐NEC. For patients treated with IP/EP (n = 160/46), the response rate was 50/28% and median OS was 13.0/7.3 months. Multivariate analysis among patients treated with IP or EP showed that the primary site (GI vs HBP; hazard ratio [HR] 0.58, 95% confidence interval [CI] 0.35–0.97) and baseline serum lactate dehydrogenase levels (not elevated vs elevated; HR 0.65, 95% CI 0.46–0.94) were independent prognostic factors for OS, while the efficacy of IP was slightly better than for EP (HR 0.80, 95% CI 0.48–1.33; P = 0.389). IP and EP are the most common treatment regimens for NEC of the digestive system. HBP primary sites and elevated lactate dehydrogenase levels are unfavorable prognostic factors for survival. A randomized controlled trial is required to establish the appropriate chemotherapy regimen for advanced NEC of the digestive system. This study was registered at UMIN as trial number 000005176.